DIVERSITY SIGNAL PROCESSING OVER WEIBULL FADING CHANNELS - V. P. Tuzlukov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
We present a moments-based approach to the performance analysis of L-branch equal-gain combining and maximal-ratio combining receivers, operating in independent or correlated, not necessarily identically distributed, Weibull fading. For both equal-gain combining and maximal-ratio combining receivers the moments of the output signal-to-noise ratio are obtained in closed-form. An accurate approximate expression is derived for the moment-generating function of the output signal-to-noise ratio of the equal-gain combining receiver utilizing the Padé approximants theory, while a closed-form expression for the corresponding MGF of the maximal-ratio combining receiver, is obtained. Significant performance criteria, such as average output signal-to-noise ratio, amount of fading and spectral efficiency at the low power regime, are extracted in closed-forms, using the moments of the output signal-to-noise ratio for both independent and correlative fading. Moreover, using the well-known moment-generating function approach, the outage and the average symbol error probability for several coherent, non-coherent, binary, and multilevel modulation schemes, are studied. The average symbol error probability of dual-branch equal-gain combining and maximal-ratio combining receivers is also obtained when correlative fading is considered in the diversity input branches. The proposed mathematical analysis is illustrated by various numerical results and validated by computer simulations.